Oral Memoirs of Clinton M. Thompson - Thompson, Clinton M. (My University, 2018)
An oral history interview with Clinton Marty Thompson, former director of both the Tulsa Medical College Library and Robert M. Bird Health Sciences Library at University of Oklahoma Health Sciences Center.
Keywords: University of Oklahoma. Tulsa Medical College -- History.; Thompson, Clinton M. -- Interviews.; Medical librarians -- Interviews.; Thompson, Clinton M. -- Career in medical librarianship.; Medical education -- Oklahoma -- History.; Medical colleges -- Oklahoma -- History.; Medical librarianship.